Cardiac Iodine-123-Meta-Iodo-Benzylguanidine Uptake in Carotid Sinus Hypersensitivity. - Maw Pin Tan; Alan Murray; Terry Hawkins; Thomas J Chadwick; Simon R J Kerr; Steve W Parry (PLoS ONE, 2015)
Carotid sinus syndrome is the association of carotid sinus hypersensitivity with syncope, unexplained falls and drop attacks in generally older people. We evaluated cardiac sympathetic innervation in this disorder in individuals with carotid sinus syndrome, asymptomatic carotid sinus hypersensitivity and controls without carotid sinus hypersensitivity.Consecutive patients diagnosed with carotid sinus syndrome at a specialist falls and syncope unit were recruited. Asymptomatic carotid sinus hypersensitivity and non-carotid sinus hypersensitivity control participants recruited from a community-dwelling cohort. Cardiac sympathetic innervation was determined using Iodine-123-metaiodobenzylguanidine (123-I-MIBG) scanning. Heart to mediastinal uptake ratio (H:M) were determined for early and late uptake on planar scintigraphy at 20 minutes and 3 hours following intravenous injection of 123-I-MIBG.Forty-two subjects: carotid sinus syndrome (n = 21), asymptomatic carotid sinus hypersensitivity (n = 12) and no carotid sinus hypersensitivity (n = 9) were included. Compared to the non- carotid sinus hypersensitivity control group, the carotid sinus syndrome group had significantly higher early H:M (estimated mean difference, B = 0.40; 95% confidence interval, CI = 0.13 to 0.67, p = 0.005) and late H:M (B = 0.32; 95%CI = 0.03 to 0.62, p = 0.032). There was, however, no significant difference in early H:M (p = 0.326) or late H:M (p = 0.351) between the asymptomatic carotid sinus hypersensitivity group and non- carotid sinus hypersensitivity controls.Cardiac sympathetic neuronal activity is increased relative to age-matched controls in individuals with carotid sinus syndrome but not those with asymptomatic carotid sinus hypersensitivity. Blood pressure and heart rate measurements alone may therefore represent an over simplification in the assessment for carotid sinus syndrome and the relative increase in cardiac sympathetic innervation provides additional clues to understanding the mechanisms behind the symptomatic presentation of carotid sinus hypersensitivity.